Contributing factors to relapse of drug addiction among clients attending rehabilitation centres of Dharan, Nepal - Sapkota, S; Khadka, A; Akela, G (Journal of Chitwan Medical College, 2017)
Relapse is the resumption of substance after a period of abstinence. It is frustrating but frequent part of recovery process. Several substance including opiates, cocaine and alcohol have particularly has high relapse rate with majority of client relapsing within 1 year following treatment. The first 90 days after treatment are very vulnerable time. Hence, the objective of the study is to assess the contributing factors to relapse of drug addiction since the aftercare services, the psycho-social aspect of the treatment has been ignored and high relapse is prevalent among the treated clients. A descriptive cross-sectional study was carried out among clients attending three rehabilitation centres of Dharan using lottery method of simple random sampling among 72 respondents using structured questionnaires from 20th September to 4th October, 2015. Findings of the study showed that majority (63.9%) of the respondents had started taking drugs again due to lack of self confidence. In addition to this another contributing factor to relapse was peer pressure (50%) followed by inability to give old habits (44.4%), easy accessibility of drugs (30.6%). The finding also indicated that there was significant relationship (p value = 0.054) between peer pressure and employment status. Lack of self-confidence, peer pressure, easy accessibility of drugs, lack of acceptance in society and family, adjustment problems had increased the chance of relapse after treatment. So, the treatment centres of Dharan should develop program that incorporate the overall development and treatment of client to prevent from relapse of drug addiction.